Penerapan Customer Relationship Management Dalam Sosial Media Untuk Mempertahankan Loyalitas Pelanggan - Andaryani, Caecilia Vita; Alifahmi, Hifni (Universitas Prof. Dr. Moestopo (Beragama), 2023)
MAPCLUB as loyalty program for customer of Pt. Mitra Adiperkasa has its main aims to maintain customer loyalty and provide rewards in the form of shopping points which can be redeemed for the next transaction. The research objective is to understand how Customer Relationship Management (CRM) increases customer loyalty through social media Instagram, using the analysis of the IDIC model from Peppers and Rogers. By using a qualitative descriptive method, researchers understand how MAPCLUB's activities manage relationships with their six million members, based on four steps of the IDIC model (Identification, Differentiation, Interaction, and Customizations) through communication in Instagram, to maintain the customer loyalty. The research’ results found several parts to improve on how they can communicate with customers based on the needs and behavior of each member. After this study of IDIC models and loyalty customer characteristics, the conclusion reveals that the optimal implementation of communication for the CRM through IDIC model to produce a better loyalty program experiences whether customers will repeat purchase, give retentions, or give referrals to other buyers.